2019
DOI: 10.2495/sc190471
|View full text |Cite
|
Sign up to set email alerts
|

Gender Considerations in Sustainable Rural Livelihood Planning: Engendering Rural Development Planning in a South African Context

Abstract: While it may be argued that worldwide women in rural areas are more likely to experience poverty than rural men and urban men and women, it is an even greater challenge for Africa. The impoverishment experienced by the communities in predominately rural areas of Africa, especially the more vulnerable segments of the population such as women, pose a significant challenge to the ensuring of their livelihoods. Furthermore, in South Africa rural women must also contend with the legacy of apartheid policies, which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Chidakwa et al 2020). As a result, women face difficulties that include, among other things, the loss of essential natural resources, food insecurity, a lack of economic opportunity, the unmet need for social services, poor education, geographical location and poor infrastructure (Gibbens & Schoeman 2019) and long-distance relationships with their husbands, who are forced to migrate in search for better opportunities in the midst of poor agro-outputs.…”
Section: Challenges Women Face In Sustaining Livelihoodsmentioning
confidence: 99%
“…Chidakwa et al 2020). As a result, women face difficulties that include, among other things, the loss of essential natural resources, food insecurity, a lack of economic opportunity, the unmet need for social services, poor education, geographical location and poor infrastructure (Gibbens & Schoeman 2019) and long-distance relationships with their husbands, who are forced to migrate in search for better opportunities in the midst of poor agro-outputs.…”
Section: Challenges Women Face In Sustaining Livelihoodsmentioning
confidence: 99%
“…Effective adaptation interventions are informed by local conditions, resources, and social needs, so the perspectives of all community members, including women, are central to their development and implementation (Mfitumukiza 2020;Gibbens and Schoeman 2019;Plan International Australia 2018) (for definitions of terms like adaptation as we use them in this working paper, see Box 1). Eriksen et al (2021) found that failure to include the perspectives of those most vulnerable and exposed to climate impacts can cause adaptation interventions to bring unintended harms.…”
Section: Box 1 | Key Definitionsmentioning
confidence: 99%
“…The inequities that women face are diverse and location-specific, because they are rooted in existing cultural norms, socioeconomic dynamics, and political and legal structures. Therefore, women must have the opportunity, for example, to identify their own unique vulnerabilities and inform interventions accordingly (Gibbens and Schoeman 2019;Gressel et al 2020).…”
Section: Box 1 | Key Definitionsmentioning
confidence: 99%